PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE PADA MATERI PERKALIAN DAN PEMBAGIAN BILANGAN CACAH SAMPAI 100.000 KELAS V SEKOLAH DASAR - Irsya Ainur Rohim; Kukuh Andri Aka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an interactive learning media based on Articulate Storyline for multiplication and division of whole numbers up to 100,000 for fifth-grade elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of the study were fifth-grade students of SD Negeri Ngadi. Data were collected through expert validation sheets, practicality questionnaires for teachers and students, and learning achievement tests in the form of pretest and posttest. The validity results showed that the media was categorized as valid by material experts and very valid by media experts. The practicality test indicated that the media was very practical, with a teacher response percentage of 100% and a student response percentage of 95%. The effectiveness of the media was analyzed using the N-Gain Score, which resulted in an average N-Gain value of 0.707, categorized as high. These results indicate that the interactive learning media based on Articulate Storyline is valid, practical, and effective for improving students’ learning outcomes in multiplication and division of whole numbers up to 100,000. Therefore, the developed media is feasible to be used as a supporting learning medium in elementary school mathematics learning.